Peran Penting Pokdarwis Dan Kualitas Sumber Daya Manusia Desa Carangwulung dalam Pengelolaan Wisata Alam Grojogan Selo Gonggo - Vicky Al-Hafiz; Firdha Amalia; Zalfaa’ Fairuuz; Dhian Satria Yudha Kartika; Ramadhan Eka Syahputra; Diva Zahwa (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2023)
The tourism potential in Carangwulung Village is very diverse and has the opportunity to be developed into a tourist attraction. There are eight tourist destinations that have been developed in Carangwulung village, one of which is the Grojogan Selo Gonggo (GSG ) nature tourism. This tourist attraction is natural attractions that come from mountain water and also pine forests. Opportunities for tourism activities at GSG are very good, if the local community and the management are able to work together to achieve the expected goals. However, the fact is that over time the people who participate in managing the GSG experience a decrease in tourism awareness. This will not affect the future development of GSG natural tourism as tourism that is of interest to tourists. Therefore, the awareness of the Carangwulung village tourism community needs to be increased again so that the development of the GSG nature tourism is not in vain and gets maximum benefits from tourism activities. The formation of POKDARWIS and improving the quality of human resources play an important role in developing GSG natural tourism, with the aim of making GSG a tourist destination that is of interest to many tourists.